Individual variation in sublethal tolerance of warming and hypoxia in the pacu Piaractus mesopotamicus: an investigation of correlations and dependence on intrinsic metabolic phenotype - Blasco, Felipe R.; Leite, Cleo A. C.; Rantin, F. Tadeu; Taylor, Edwin W.; McKenzie, David J. (Frontiers in Fish Science, 2024)
We evaluated interindividual variation in traits of warming and hypoxia tolerance in a cohort (n = 24) of juvenile pacu Piaractus mesopotamicus, acclimated to 26 °C, to investigate whether individuals tolerant to warming were also tolerant to hypoxia, and whether individual tolerance depended on body mass or intrinsic traits of aerobic metabolism. Two traits of warming tolerance were measured, the critical thermal maximum (CTmax) in a static tank with loss of equilibrium as endpoint, and the critical thermal maximum for aerobic swimming (CTSmax) in a swim tunnel with fatigue as endpoint. Two traits of hypoxia tolerance were derived by static respirometry during progressive hypoxia, the critical saturation for regulation of standard metabolic rate (Scrit) and the regulation index (RI). At 39.7 ± 0.4 °C (mean ± SD), CTmax was significantly higher than CTSmax, at 38.0 ± 1.0 °C. Both traits had very low coefficient of variation within the cohort (CV, 1.1 and 2.6 %, respectively) and CTmax was not correlated with any other trait. Individual Scrit (18.5 ± 7.2 % saturation, CV 38.9 %) and RI (76.0 ± 16.1 % regulation, CV 45.6 %) were correlated (R = 0.686) and both were significantly correlated with CTSmax (R = 0.472 and 0.475, respectively). This indicates that individuals tolerant to warming were also tolerant to hypoxia although two individuals with low CTSmax were drivers of the correlations against Scrit and RI. The CTmax, CTSmax and Scrit showed no dependence on body mass but RI increased with mass (R 2 = 0.286), indicating that larger individuals were more tolerant to hypoxia. When corrected for body mass, RI was no longer correlated with CTSmax, further revealing that the correlations were rather tenuous. Finally, we found no evidence that individual tolerance was dependent on intrinsic traits of aerobic metabolism. The results indicate that sublethal indicators, such as CTSmax, Scrit and RI, can be useful in exploring correlations among traits of tolerance to warming and hypoxia in fishes, but more studies on more species are required with larger sample sizes to confirm these results and to reveal if there are general patterns.